2017
DOI: 10.1002/lary.26706
|View full text |Cite
|
Sign up to set email alerts
|

Treatment effectiveness for aging changes in the larynx

Abstract: 4. Laryngoscope, 127:2572-2577, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Allensworth et al found a significant improvement in the VHI-30 (59.4-31.5) in 10 patients, which was very similar to the improvement found in our study (55.8-30.9) [20]. Contrary to our study where we only found an impact on fundamental frequency (males) and a transient effect in the dynamic range (patients with atrophy only), both Sachs and Allensworth showed improvements in several of the (semi-)objective parameters they analyzed [18,20]. As for patients with sulcus/scar, Welham et al showed a significant improvement in VHI-30 after treatment with thyroplasty in his series which did include unilateral procedures.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Allensworth et al found a significant improvement in the VHI-30 (59.4-31.5) in 10 patients, which was very similar to the improvement found in our study (55.8-30.9) [20]. Contrary to our study where we only found an impact on fundamental frequency (males) and a transient effect in the dynamic range (patients with atrophy only), both Sachs and Allensworth showed improvements in several of the (semi-)objective parameters they analyzed [18,20]. As for patients with sulcus/scar, Welham et al showed a significant improvement in VHI-30 after treatment with thyroplasty in his series which did include unilateral procedures.…”
Section: Discussionsupporting
confidence: 89%
“…Shortly after this, Gore-tex ® medialization thyroplasty was introduced [11,14]. Since then several studies have reported on bilateral medialization thyroplasty in patients with glottic incompetence as a result of atrophy and sulcus, as well as paralysis, paresis, and other causes [6,7,[14][15][16][17][18][19][20][21][22][23]. The largest patient group (total n = 75, hypomobility n = 27, paresis n = 16, scarring n = 18, atrophy n = 14), which also has the longest follow-up (up to 10 years), showed overall improvement in voice-related quality of life (VRQOL).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment of voice problems in the elderly can be beneficial for both voice outcomes and voice-related quality of life. 8 , 10 - 13 Optimizing management of voice problems in this patient population has important quality-of-life and health implications. Most studies have focused on patients identified through specialized otolaryngology or voice clinics and do not include self-reported voice improvement.…”
mentioning
confidence: 99%